Pembangunan Modal Insan Melalui Kurikulum Pusat Asuhan Tunas Islam Malaysia: Human Development through Islamic Preschool Curriculum at Pusat Asuhan Tunas Islam (PASTI) - Hj Siren, Nor Raudah; Yusoff, Salmee Suhaina (Jurnal Usuluddin, 2020)
Islamic education, introduced for childhood, is very important in shaping the identity of muslim in young children. Education for young children in this life requires specific models and methods in order to produce human capital capable of high godly devotion to Allah Almighty. Therefore, this article has analyzed the preschool curriculum implemented at the Pusat Asuhan Tunas Islam (PASTI) to see how PASTI develops the curriculum and implements the curriculum in an effort to foster the virtues of children. The analysis found that the PASTI curriculum is still within the framework of National curriculum development because it has components of cognitive development, language and communication development, psychomotor development and socioemotional development. However PASTI has implemented the process of teaching and learning in an interdisciplinary manner according to its vision and mission of education.